(untitled) (Global Journal of Medical Research, 2023)
Intraosseous synovial cysts (ISCs) are rare occurrences characterized by synovial proliferation within the bone. This article presents a case report of a 19-year-old patient with a carpal scaphoid bone fracture and an incidentally detected intraosseous cyst. The patient underwent surgical treatment involving careful curettage of the cystic cavity, addition of a spongy bone graft, and fracture stabilization. The histopathological examination confirmed the presence of an intraosseous synovial cyst. The patient achieved a satisfactory functional outcome, with early consolidation and resumption of daily activities. The study emphasizes the importance of accurate diagnosis and appropriate surgical management, highlighting the favorable prognosis and rarity of recurrences in intraosseous synovial cysts of the scaphoid bone.